Is it possible to improve memory function by upregulation of the cholesterol 24S-hydroxylase (CYP46A1) in the brain? - Silvia Maioli; Ann Båvner; Zeina Ali; Maura Heverin; Muhammad-Al-Mustafa Ismail; Elena Puerta; Maria Olin; Ahmed Saeed; Marjan Shafaati; Paolo Parini; Angel Cedazo-Minguez; Ingemar Björkhem; et al. (PLoS ONE, 2013)
We previously described a heterozygous mouse model overexpressing human HA-tagged 24S-hydroxylase (CYP46A1) utilizing a ubiquitous expression vector. In this study, we generated homozygotes of these mice with circulating levels of 24OH 30-60% higher than the heterozygotes. Female homozygous CYP46A1 transgenic mice, aged 15 months, showed an improvement in spatial memory in the Morris water maze test as compared to the wild type mice. The levels of N-Methyl-D-Aspartate receptor 1, phosphorylated-N-Methyl-D-Aspartate receptor 2A, postsynaptic density 95, synapsin-1 and synapthophysin were significantly increased in the hippocampus of the CYP46A1 transgenic mice as compared to the controls. The levels of lanosterol in the brain of the CYP46A1 transgenic mice were significantly increased, consistent with a higher synthesis of cholesterol. Our results are discussed in relation to the hypothesis that the flux in the mevalonate pathway in the brain is of importance in cognitive functions.